1999
DOI: 10.1097/00004647-199901000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Protein Kinases in Canine Basilar Artery in Vasospasm

Abstract: Subarachnoid hemorrhage (SAH) often leads to a long-term narrowing of cerebra! artery called vasospasm. To understand the molecular mechanisms in vasospasm, signal transduction of tyrosine kinase pathway and phosphorylation of myosin light chain (MLC) and calponin (CaP) in the basilar artery were studied. Vasospasm was produced in the canine basilar artery by a two-hemorrhage method, and vasocontraction was induced by a local application of KCI or serotonin to the basilar artery after a transclival exposure. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 46 publications
(16 reference statements)
4
32
0
Order By: Relevance
“…In the posterior ciliary arteries, the 5-HT-induced response of increased [Ca 2+ ] i was effected by both the Ca 2+ influx from extracellular spaces and its release from internal stores, whereas the [Ca 2+ ] i increase in the vorticose veins was much more dependent on the Ca 2+ influx from extracellular spaces. Furthermore, the activation of smooth muscle contraction is thought to occur through increases in the [Ca 2+ ] i , activation of Ca 2+ / calmodulin-dependent MLCK, and increases in MLC phosphorylation, as in the spastic canine basilar artery, where MLC has been shown to be phosphorylated by MLCK (22,38). Our results using a MLCK inhibitor in both arteries and veins were consistent with this model.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the posterior ciliary arteries, the 5-HT-induced response of increased [Ca 2+ ] i was effected by both the Ca 2+ influx from extracellular spaces and its release from internal stores, whereas the [Ca 2+ ] i increase in the vorticose veins was much more dependent on the Ca 2+ influx from extracellular spaces. Furthermore, the activation of smooth muscle contraction is thought to occur through increases in the [Ca 2+ ] i , activation of Ca 2+ / calmodulin-dependent MLCK, and increases in MLC phosphorylation, as in the spastic canine basilar artery, where MLC has been shown to be phosphorylated by MLCK (22,38). Our results using a MLCK inhibitor in both arteries and veins were consistent with this model.…”
Section: Discussionsupporting
confidence: 85%
“…10c). The effect of PKI (14)(15)(16)(17)(18)(19)(20)(21)(22) (2 μM) was the same as that observed in the presence of H-89 (n = 8) (data not shown). SQ22536 (100 μM) also completely blocked this increase (n = 8) (Fig.…”
Section: + ] I Increase In Vorticose Veinssupporting
confidence: 63%
See 1 more Smart Citation
“…2,20 MAPK activity was elevated in canine basilar arteries in a double-hemorrhage model of experimental cerebral vasospasm. 27 This study for the first time demonstrated that PTK and MAPK are involved in ET-1-induced contraction in cerebral arteries. Since both hemolysate and ET-1 are extremely important spasmogens for cerebral vasospasm 1,2 and PTK and MAPK are involved in the signal transduction of both hemolysate 2,20 and ET-1 (this study), PTK and MAPK may be important factors in the pathogenesis of cerebral vasospasm.…”
Section: Role Of Ptk Mapk and Pkc In Cerebral Vasospasmmentioning
confidence: 73%
“…No attempt was made to remove endothelial cells. The modified Krebs-Henseleit solution contained the following (mmol/L): NaCl 120, KCl 4.5, MgSO 4 1, NaHCO 3 27, KH 2 PO 4 1, CaCl 2 2.5, and dextrose 10. All procedures were approved by the Animal Care and Use Committee at the University of Mississippi Medical Center.…”
mentioning
confidence: 99%